Temporal variability and environmental availability of inorganic constituents in an Antarctic marine sediment core from a polynya area in the Ross Sea - MALANDRINO, Mery; MENTASTI, Edoardo; GIACOMINO, AGNESE; ABOLLINO, Ornella; E. Dinelli; S. Sandrini; L. Tositti (Toxicological & Environmental Chemistry, 2010)
Marine sediments are sinks and repositories of matter recirculated in the environment by a number of different processes. They behave as environmental archives, providing a key to the understanding of the processes occurring in a given region in the course of time. In this work, we characterized the inorganic composition of a surface sediment core collected in the polynya of Terra Nova Bay (TNB) in the Ross Sea, an area of major environmental interest as it hosts a number of crucial processes connecting atmospheric transport with the Southern Ocean system. The total concentrations of major, minor, and trace elements were determined. The results were treated with chemometric techniques. In order to investigate the environmental mobility of several elements, the modified Bureau of Community Reference (BCR) three-step sequential extraction procedure was applied and the partitioning of eight metals (Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn) into different fractions was determined. The knowledge of the metal distribution across this Antarctic sediment core allowed us to assess long-term climatic changes and possible natural background values in this specific environment. Furthermore, the results showed a separation between higher and lower sections of the core that suggests a stronger fingerprint from biogenic and geological processes, respectively.